Is life satisfaction associated with the purpose in life of elderly hydrogymnastics practitioners? - Daniel Vicentini de Oliveira; Cristina Cristovão Ribeiro; Rafael Eduardo Rosa Pico; Matheus Oliveira Murari; Gabriel Lucas Morais Freire; Andressa Ribeiro Contreira; José Roberto Andrade do Nascimento Júnior (Universidade Estadual Paulista (UNESP), 2019)
Abstract Aim: This cross-sectional study aimed to investigate the association between life satisfaction and purpose in the life of the elderly hydro gymnastic practitioners. Methods: A total of 92 older people of both sexes, who practice hydro gymnastics in the city of Maringá, State of Paraná, Brazil, participated in the study. A sociodemographic questionnaire, the Satisfaction with Life Scale and the purpose in life Questionnaire were used as instruments. Data analysis was carried out by using Kolmogorov-Smirnov test, Mann-Whitney U test, Kruskal-Wallis test, and Spearman's correlation test, in addition to the Path Analysis (p <0.05). Results: The results showed a greater life satisfaction for the women comparing to the men (p = 0.023). Moreover, it was found that the elderly who perceived themselves with a better health condition obtained higher scores according to the purpose in life scale. Life satisfaction had a positive and moderate association (β = 0.24) with the purpose in the life of the elderly, which explains 6% of the variability. Conclusion: It was concluded that sex can be considered as an intervening factor when concerning life satisfaction, time of practice of hydro gymnastics and self-perceived health related to the purpose in life of the elderly. In addition, satisfaction with life was positively associated with the purpose in the life.